PENGARUH KOMUNIKASI DAN K3 (KESELAMATAN & KESEHATAN KERJA) TERHADAP KINERJA KARYAWAN DI PT. KARYAINDO SEJATITAMA KECAMATAN SUKU TENGAH LAKITAN ULU TERAWAS KABUPATEN MUSI RAWAS - Supriyanto Supriyanto; Gunadi Gunadi; Sardiyo Sardiyo; Soadah Soadah; Stela Anggraini (LPPM UNIVERSITAS BINA INSAN, 2020)
This study aims to determine the influence of Employee Performance at PT. Karyaindo Sejatitama Suku Tengah Lakitan Ulu Terawas Subdistrict, Musi Rawas Regency. Technique of data collecting were observation, interview, questionnaire, and documentation. The sample of this study used saturated sampling, that was all 96 employees. Technique of data analysis is done by testing the validity test and reliability test, the classic assumption test consists of normality test, linearity test, linear regression test, correlation test, determination test, and hypothesis test. Based on the t test, the value of tcount (10,944) > ttable (1,986) then Ho is rejected and Ha is accepted. This means that communication has a significant influence on employee performance at PT. Karyaindo Sejatitama Suku Tengah Lakitan Ulu Terawas Subdistrict, Musi Rawas Regency. Based on the t test, the value of tcount (8.691) > t ttable (1.986) then Ho is rejected and Ha is accepted. This means that K3 has a significant influence on Employee Performance at PT. Karyaindo Sejatitama Suku Tengah Lakitan Ulu Terawas Subdistrict, Musi Rawas Regency. Based on the F test, the value of Fcount (69.343) > Ftable (3.09) then Ho is rejected and Ha is accepted. This means that Communication and Health and Safety (Occupational Health & Safety) has a significant influence on Employee Performance at PT. Karyaindo Sejatitama, Suku Tengah Lakitan Ulu Terawas Subdistrict, Musi Rawas Regency.